STRATEGI PEMBELAJARAN BAHASA ARAB BERBASIS KURIKULUM MERDEKA PADA PESERTA DIDIK SEKOLAH DASAR (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to examine Arabic language learning strategies based on the Merdeka Curriculum for elementary school students. Arabic language learning at the elementary level plays an important role as an initial foundation for language mastery as well as for fostering positive attitudes toward Arabic. However, in practice, various challenges are still found, such as low student learning motivation and the use of learning strategies that are not fully aligned with children’s characteristics. This study employs a qualitative approach using a library research design. Data were collected from official Merdeka Curriculum documents, learning outcomes frameworks, textbooks, scholarly journal articles, and relevant previous studies. Data collection was conducted through documentation, while data analysis used descriptive qualitative analysis. The findings indicate that Arabic learning strategies based on the Merdeka Curriculum emphasize student-centered learning, differentiated instruction, contextual learning approaches, and the integration of Pancasila Student Profile values. These strategies contribute to increasing students’ active participation and making learning more meaningful. With adequate teacher competence and a supportive learning environment, Arabic language learning in elementary schools can be effectively implemented in accordance with the principles of the Merdeka Curriculum.